The Communist manifesto - Marx, Karl, 1818-1883; Engels, Friedrich, 1820-1895 (Yale University Press, 2012)
Contains the "Communist Manifesto," several essays discussing the historical background of the manifesto and its influence today, all of the prefaces to the manifesto used during Marx and Engels' lifetime, and Engels' "Principles of Communism."
Keywords: Marx, Karl, -- 1818-1883. -- Manifest der Kommunistischen Partei.; Manifest der Kommunistischen Partei (Marx, Karl); Communism.; POLITICAL SCIENCE -- Political Ideologies -- Communism & Socialism.; PHILOSOPHY -- Political.; Communism; dissertations.; Academic theses; Academic theses.; Thèses et écrits académiques.